The age-friendly public health center satisfaction scale: development and psychometric evaluation. Issue 4 (31st August 2021) - Baithesda, Baithesda; Chen, Ching-Min; Juniarti, Neti; Tandilangi, Abigail Asfas
Abstract : Purpose: The study aimed to develop a reliable and valid instrument that could be used to assess the age-friendly Public Health Center Satisfaction (APHCS) among older people. Design/methodology/approach: A cross-sectional study was performed to assess the psychometric properties of the scale. The study was conducted in Manado City, Indonesia, from August to November of 2019 using stratified random sampling. A review of the literature and content analysis identified subscales and items to be included in the instrument. The 268 participants aged = 60 years were completed for psychometric evaluation with a response rate of 83.8%. Data were analyzed with descriptive statistics, Exploratory Factor Analysis (EFA), Cronbach's Alpha, t -test, one-way ANOVA, and Person/Spearmen correlations. Findings: The final scale consists of a three-factor structure with 16 items, which were accounted for 68.99% of the total variation in response. The Cronbach's alpha of the total APHCS was 0.88, which indicated the high reliability and acceptance of the instrument. Also, the concurrent validity was demonstrated by the significant differences in mean and associations among the APHCS scale, the age-friendly Public Health Center (PHCC) utilization, and individual variables, with r ranging from −0.13 to 0.30 ( p  < 0.05). Research limitations/implications: Older people are more likely to use PHCCs than others, and they have higher expectations about health services. This study has highlighted the need for action on the quality of healthcare by providers and national authorities. High-quality primary healthcare that sees clients as partners, considering the needs and capacities of elderly clients should be provided as standard. The APHCS scale can enhance our understanding of elderly satisfaction toward the age-friendly PHCC program. Also, the instrument can be used for monitoring and measuring institutions, which is a basis for policymakers to improve and develop the age-friendly PHCC program. Originality/value: The APHCS scale is a valid and reliable instrument for getting information about the satisfaction of the elderly toward the age-friendly PHCC program.